A 1, 8-naphthalimide–pyridoxal conjugate as a supramolecular gelator for colorimetric read out of F− ions in solution, gel and solid states. (23rd January 2019) - Pati, Chiranjit; Ghosh, Kumaresh
Abstract : Naphthalimide–pyridoxal conjugated gelator1 has been designed and synthesized. Compound1 which forms stable greenish yellow colored gel in DMSO : H2 O (8 : 1 v/v), shows selective sensing of F − in solution, gel and solid states under different conditions. Abstract : A naphthalimide–pyridoxal conjugate1 has been designed and synthesized. Compound1 forms a stable greenish yellow colored gel in DMSO : H2 O (8 : 1 v/v). Rheological study reveals that the gel is mechanically strong ( G ′> G ′′) over a wide range of applied strains. The morphology of the gel as determined by FESEM shows a highly cross-linked fibrous network. The gel is anion-responsive and is selectively transformed into a sol with a color change from greenish yellow to deep blue only in the presence of F − among other anions. In CH3 CN, compound1 was also sensitive to basic anions such as F − and AcO − ions. In solution, F − was differentiated from AcO − through a color change. While the yellow colored solution of1 in acetonitrile was changed into deep blue in the presence of F −, AcO − ions gave a faint blue coloration. A similar colorimetric differentiation of F − from AcO − has been possible in CH3 CN by a reusable Schiff base-linked Merrifield resin1a or1b .